Light-emitting device, preparation method thereof and display device
By using doped zinc oxide and long carbon chain ligands in the electron transport layer of the light emitting device, the interface problem of the zinc oxide electron transport layer is solved, the luminescence efficiency and life are improved, and more efficient electron migration and carriers are achieved. injection.
Patent Information
- Application Number
- CN202310849021.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing zinc oxide as an electron transport layer has quenched quantum dots, uneven interfaces and poor electron injection properties in the light emitting device, which affects the luminescent performance.
The first electron transport layer material is used as a long carbon chain ligand with 4 to 12 carbon atoms connected to the second electron transport layer, and the zinc oxide is prevented from contacting the surface of the luminescent layer material through the steric hindrance effect. , improve conductivity and reduce work function.
The electron mobility and luminescence efficiency are improved, the device's working voltage is reduced, and the carrier injection balance is enhanced, thereby improving the efficiency and life of the light emitting device.
Smart Images

Figure CN119317310A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of optoelectronic technology, and in particular to a light-emitting device and a method for preparing the same, and a display device. Background Art
[0002] The light-emitting devices widely used at present are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). The traditional OLED and QLED device structures mainly include an anode, a hole functional layer, a light-emitting layer, an electron functional layer, and a cathode. Under the action of the electric field, the holes generated by the anode of the light-emitting device and the electrons generated by the cathode move and are injected into the hole transport layer and the electron transport layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, and finally visible light is generated.
[0003] The first doped zinc oxide includes zinc oxide, a first doping metal and a second doping metal, wherein the first doping metal includes one or more of Li, Be, Mg, Al, K, and Ca, and the second doping metal includes one or more of Ga, Cd, In, and Sn; and / or the second doped zinc oxide includes zinc oxide and a third doping element, and the third doping element includes one or more of Mg, Al, Ga, Li, K, Cd, In, and Sn.
[0004] Optionally, in some embodiments of the present application, in the first electron transport layer, the molar ratio of the first doped metal to the total metal elements is (1 to 20):100; and / or in the first electron transport layer, the molar ratio of the second doped metal to the total metal elements is (1 to 20):100.
[0005] Optionally, in some embodiments of the present application, the long carbon chain ligand includes one or more of C4-C12 carboxylic acid ligands, C4-C12 thiol ligands, C4-C12 amine ligands, and C4-C12 phosphate ligands; and / or among the ligands connected to the zinc oxide or doped zinc oxide, the molar ratio of the long carbon chain ligand to all ligands on the surface of zinc oxide is greater than or equal to 20%.
[0006] Optionally, in some embodiments of the present application, the C4~C12 carboxylic acid ligands include one or more of butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, n-octanoic acid, n-decanoic acid, undecanoic acid, dodecanoic acid (lauric acid), etc.; and / or the C4~C12 thiol ligands include one or more of butyl mercaptan, hexyl mercaptan, 1-heptyl mercaptan, n-octyl mercaptan, isooctyl mercaptan, 1-decyl mercaptan, 1-undecanethiol, 1-dodecanethiol, 1-pentyl mercaptan, etc.; and / or the C4~C12 amine ligands include one or more of n-butylamine, pentylamine, hexylamine, heptylamine, n-octylamine, decylamine, 1-aminoundecane, dodecylamine, etc.; and / or the C4~C12 phosphate ligands include one or more of n-hexyl phosphate, 1-octyl phosphate, 1-decyl phosphate, n-dodecyl phosphoric acid, etc.
[0007] Optionally, in some embodiments of the present application, the first doped zinc oxide is selected from gallium-lithium co-doped zinc oxide, and the zinc oxide or the second doped zinc oxide is connected to one or more of n-octylamine, dodecanoic acid, butanethiol, and 1-decyl phosphoric acid.
[0008] Optionally, in some embodiments of the present application, the thickness of the first electron transport layer is 5 to 40 nm; and / or the thickness of the second electron transport layer is 5 to 40 nm; and / or
[0009] The material of the light-emitting layer is selected from one or more of organic light-emitting materials or quantum dot materials; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the Group II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZ nS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, Hg At least one of ZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb , at least one of GaPAs, GaPSb, AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNPs, InNAs, InNSb, InPAs, InPSb, GaAlNPs, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNPs, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNPs, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or
[0010] The cathode and the anode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, ITZO, ICO, A At least one of MO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS; and / or
[0011] The light emitting device further comprises a hole functional layer, wherein the hole functional layer is arranged between the anode and the light emitting layer, and the hole functional layer comprises at least one layer of a hole injection layer and a hole transport layer, and the material of the hole transport layer is selected from arylamine, polyaniline, polypyrrole, poly(p-)phenylene vinylene and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives Its derivatives, poly (spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN one or more; wherein the aromatic amine is selected from 4,4'-bis (9-carbazole) biphenyl, poly (9,9-dioctylfluorene-CO-N- (4-butylphenyl) diphenylamine), poly (N,N'-bis (4-butylphenyl) -N,N'-bis (phenyl) benzidine), N,N'-bis (4- (N,N'-diphenyl-amino) triphenylamine, 4,4',4"-tri(carbazol-9-yl)triphenylamine, 4,4',4"-tri(N-carbazolyl)triphenylamine, 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, -diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, Spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene];The material of the hole injection layer is selected from poly(ethylenedioxythiophene): polystyrene sulfonate, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine, 4,4',4 "-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with F4-TCNQ, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, transition metal oxides, transition metal sulfur compounds, one or more thereof; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, CuO; the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, CuS; and / or;
[0012] The electronic functional layer also includes an electron injection layer, which is arranged close to the cathode, wherein the material of the electron injection layer includes one or more of LiF, LiF / Yb, MgP, MgF2, Al2O3, Ga2O3, ZnO, Cs2CO3, Rb2CO3, and RbBr.
[0013] Correspondingly, an embodiment of the present application also provides a method for preparing a light-emitting device, the preparation method comprising: providing a cathode; setting an electronic functional layer on the cathode; forming a light-emitting layer on the electronic functional layer; forming an anode on the light-emitting layer; or, the preparation method comprises: providing a preset device, the preset device comprising a stacked anode and a light-emitting layer; forming an electronic functional layer on the preset device; forming a cathode on the electronic functional layer; wherein the electronic functional layer comprises a first electron transport layer and a second electron transport layer, the first electron transport layer is arranged close to the cathode, and the second electron transport layer is arranged close to the light-emitting layer, the material of the first electron transport layer comprises a first doped zinc oxide, the material of the second electron transport layer comprises zinc oxide or a second doped zinc oxide, and the zinc oxide or the second doped zinc oxide is connected to a long carbon chain ligand with 4 to 12 carbon atoms.
[0014] Optionally, in some embodiments of the present application, the electronic functional layer is set on the cathode, including: providing a first solution and a second solution, the first solution including a first metal source, an organic amine and a first solvent, the first metal source including a first zinc source, a first doped metal source and a second doped metal source, the second solution including a zinc oxide nanomaterial and a second solvent, the zinc oxide nanomaterial is selected from zinc oxide or a second doped zinc oxide; refluxing the first solution to obtain a first sol; setting the first sol on the cathode, annealing to obtain the first electron transport layer; setting the second solution on the first electron transport layer to obtain the second electron transport layer; or, forming the electronic functional layer on the preset device includes: providing a first solution and a second solution, the first metal source including a first zinc source, a first doped metal source and a second doped metal source, the second solution including a zinc oxide nanomaterial and a second solvent, the zinc oxide nanomaterial is selected from zinc oxide or a second doped zinc oxide; refluxing the first solution to obtain a first sol; setting the second solution on the preset device to obtain the second electron transport layer; setting the first sol on the second electron transport layer, annealing to obtain the first electron transport layer.
[0015] Optionally, in some embodiments of the present application, the temperature of the annealing treatment is 150-500° C.; and / or the time of the annealing treatment is 5-120 minutes; and / or the annealing treatment is performed in a dry air atmosphere.
[0016] Optionally, in some embodiments of the present application, the temperature of the reflux reaction is 50-80°C; and / or the time of the reflux reaction is 3-12h; and / or the first zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, zinc laurate and zinc oxide; and / or the first doping metal source includes one or more of Li source, Be source, Mg source, Al source, K source, Ca source; and / or the second doping metal source includes one or more of Ga source, Cd source, In source, Sn source; and / or the first doping metal element in the first doping metal source and the second doping metal element in the first doping metal source are mixed with each other. The molar ratio of the metal element in the first metal source is (1-20):100; and / or the molar ratio of the second doped metal element in the second doped metal source to the metal element in the first metal source is (1-20):100; and / or in the first solution, the molar concentration of the metal element in the first metal source is 0.1-1 mmol / mL; and / or the organic amine includes one or more of ethanolamine, diethanolamine, and 3-aminopropanol; and / or the molar ratio of the organic amine to the first metal source is 1:1.3-1.3:1; and / or the first solvent is selected from alcohol solvents.
[0017] Optionally, in some embodiments of the present application, the preparation method also includes preparing zinc oxide nanomaterials, and the preparation of zinc oxide nanomaterials includes: providing a third solution, the third solution including a second metal source, a ligand solvent and a third solvent, wherein the second metal source includes a second zinc source or the second metal source includes a second zinc source and a third doped metal source, and the carbon chain length of the ligand solvent is 4 to 12 carbon atoms; adding a base to the third solution, and mixing and reacting at room temperature to obtain zinc oxide or doped zinc oxide.
[0018] Optionally, in some embodiments of the present application, the ligand solvent includes one or more of a C4-C12 carboxylic acid solvent, a C4-C12 thiol solvent, a C4-C12 amine solvent, and a C4-C12 phosphoric acid solvent; and / or the second metal source includes a second metal cation and a second anion, wherein the molar ratio of the ligand solvent to the second anion is greater than or equal to 40%; and / or the second zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, and zinc laurate; and / or the third doping metal source includes one or more of a Mg source, an Al source, a Ga source, a Li source, a K source, a Cd source, an In source, and a Sn source; and / or the third solvent includes one or more of dimethyl sulfoxide, NN-dimethylformamide, tetrahydrofuran, and an alcohol solvent; and / or the base includes one or more of lithium hydroxide, sodium hydroxide, and triethylamine; and / or the mixing reaction time is 5 to 15 hours.
[0019] Optionally, in some embodiments of the present application, after the second solution is provided, drying is further included, and the drying is heating drying or vacuum drying, wherein the heating drying temperature is 60 to 150° C., and the vacuum drying pressure is 10 -1 ~10 -2 Pa, the vacuum drying temperature is 0-30° C.; and / or the second solvent is selected from alcohol solvents; and / or in the second solution, the concentration of the zinc oxide nanomaterial is 10-50 mg / mL.
[0020] Correspondingly, an embodiment of the present application further provides a display device, comprising the above-mentioned light-emitting device, or comprising a light-emitting device prepared by the above-mentioned preparation method.
[0021] The light-emitting device of the present application, the electronic functional layer includes a first electron transport layer and a second electron transport layer, the material in the first electron transport layer close to the cathode side includes a first doped zinc oxide, which increases the electron mobility; and the zinc oxide in the second electron transport layer close to the light-emitting layer side or the second doped zinc oxide is connected to a long carbon chain ligand with 4 to 12 carbon atoms, which can improve the electrical conductivity and reduce the work function, and prevent the surface contact between the zinc oxide and the material of the light-emitting layer through the steric hindrance effect, thereby inhibiting the dissociation of excitons at the interface between the light-emitting layer and the electronic functional layer, thereby improving the efficiency and luminescence performance of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 A structural schematic diagram of an embodiment of a light emitting device is provided for the present application;
[0024] Figure 2 A schematic diagram of a process of an embodiment of a method for preparing a light-emitting device provided in the present application;
[0025] Figure 3 A schematic flow chart of another embodiment of the method for preparing a light-emitting device provided in the present application.
[0026] Figure numerals: 100 - light-emitting device; 10 - anode; 20 - cathode; 30 - light-emitting layer; 40 - electron functional layer; 41 - first electron transport layer; 42 - second electron transport layer; 43 - electron injection layer; 50 - hole functional layer, 51 - hole injection layer, 52 - hole transport layer. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.
[0028] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0029] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0030] Nano zinc oxide (ZnO) is widely used as an electron transport material in light-emitting devices because its conduction band energy level is conducive to the injection of electrons from the cathode to the light-emitting layer, and its deeper valence band energy level can effectively block holes. However, the current zinc oxide used as an electron transport layer still has quenching quantum dots, uneven interfaces, poor electron injection, etc., which affects the luminescence performance of the light-emitting device.
[0031] Based on this, the present application provides a light emitting device, referring to Figure 1 , Figure 1 A structural schematic diagram of an embodiment of a light-emitting device is provided for the present application. The light-emitting device 100 includes an anode 10 and a cathode 20 arranged opposite to each other, and a light-emitting layer 30 arranged between the anode 10 and the cathode 20, and an electronic functional layer 40 is arranged between the cathode 20 and the light-emitting layer 30.
[0032] Among them, the electronic functional layer 40 includes a first electron transport layer 41 and a second electron transport layer 42, the first electron transport layer 41 is arranged close to the cathode 20 side, and the second electron transport layer 42 is arranged close to the light-emitting layer 30 side, the material of the first electron transport layer 41 includes a first doped zinc oxide, and the material of the second electron transport layer 42 includes zinc oxide or a second doped zinc oxide, and the zinc oxide or the second doped zinc oxide is connected to a long carbon chain ligand with 4 to 12 carbon atoms.
[0033] In this embodiment, the material in the first electron transport layer 41 includes a first doped zinc oxide, which increases the electron mobility; and the zinc oxide in the second electron transport layer 42 or the second doped zinc oxide is connected to a long carbon chain ligand with a carbon chain length of 4 to 12 carbon atoms, which can improve the conductivity and reduce the work function. While increasing the electron mobility, the surface contact between the zinc oxide and the material of the light-emitting layer 30 is prevented through the steric hindrance effect, thereby inhibiting the dissociation of excitons at the interface between the light-emitting layer 30 and the electronic functional layer 40, thereby improving the recombination efficiency of the light-emitting device 100, thereby improving the efficiency and luminescence performance of the light-emitting device 100.
[0034] Furthermore, improving the conductivity is beneficial to the transmission of electrons and can reduce the operating voltage of the device, while reducing the work function is beneficial to the injection of electrons and makes the carrier injection more balanced, thereby increasing the efficiency of the light-emitting device 100.
[0035] In one embodiment, the first doped zinc oxide includes zinc oxide, a first doping metal and a second doping metal, wherein the first doping metal includes one or more of Li, Be, Mg, Al, K, and Ca, and the second doping metal includes one or more of Ga, Cd, In, and Sn.
[0036] The electronegativity and atomic radius of the second doped metal are close to those of zinc, and the work function of the first electron transport layer 41 can be reduced without introducing lattice defects. Since the first doped metal has a small atomic radius, interstitial zinc defects can be eliminated through interstitial doping, thereby improving the conductivity without changing the work function and the valence band edge.
[0037] In one embodiment, in the first electron transport layer, the molar ratio of the first doping metal to the total metal elements is (1-20):100, and can be specifically (1-15):100, (5-15):100, (5-13):100, (8-13):100, (8-10):100, etc.
[0038] In one embodiment, in the first electron transport layer, the molar ratio of the second doping metal to the total metal elements is (1-20):100, and can be specifically (1-15):100, (5-15):100, (5-13):100, (8-13):100, (8-10):100, etc.
[0039] In the above two embodiments, the total metal elements are the sum of the metal elements contained in the first electron transport layer.
[0040] In a specific embodiment, the first doping metal is selected from Li, and the second doping metal is selected from Ga. Furthermore, in the first electron transport layer, the molar ratio of gallium element (Ga) to total metal elements may be 10:100, and the molar ratio of lithium (Li) element to total metal elements may be 10:100.
[0041] In one embodiment, the first electron transport layer 41 is prepared by a sol-gel method. The sol-gel method is a method in which a compound containing highly chemically active components is solidified through a solution, sol, and gel, and then heat-treated to form an oxide or other compound solid. Specifically, an inorganic substance or a metal salt is used as a precursor, and these raw materials are uniformly mixed in the liquid phase, and hydrolysis and condensation chemical reactions are carried out to form a stable transparent sol system in the solution. After aging of the sol, the colloid particles slowly polymerize to form a gel with a three-dimensional spatial network structure, and the gel network is filled with a solvent that loses fluidity to form a gel. The gel is dried, sintered, and solidified to prepare a nanomaterial.
[0042] In this embodiment, the sol-gel method can improve the effective incorporation of the first doped metal and the second doped metal, and the high-temperature post-annealing process in the sol-gel method can significantly improve the crystallinity of the film layer, thereby improving the electron mobility of the first electron transport layer 41.
[0043] In one embodiment, in the second electron transport layer 42, the doped zinc oxide includes zinc oxide and a third doping element, and the third doping element includes one or more of Mg, Al, Ga, Li, K, Cd, In, and Sn. Specifically, the molar ratio of the third doping element to the zinc oxide is greater than 0 and less than or equal to 10%, and the molar ratio is calculated in terms of Y, then 0<Y≤10%, specifically 0<Y≤1%, 1%≤Y≤3%, 3%≤Y≤5%, 5%≤Y≤8%, 8%≤Y≤10%, etc. The third doping element and zinc oxide of the molar ratio can have good electron transport performance.
[0044] In one embodiment, the long carbon chain ligand includes one or more of C4-C12 carboxylic acid ligands, C4-C12 thiol ligands, C4-C12 amine ligands, and C4-C12 phosphate ligands. In this embodiment, the long carbon chain ligand with a carbon atom length of 4 to 12 can form a steric hindrance effect, has good stability and relatively good charge conductivity, and avoids poor charge conductivity that hinders electron transmission and causes the operating voltage of the light-emitting device 100 to be too high.
[0045] Specifically, the C4-C12 carboxylic acid ligands include one or more of butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, n-octanoic acid, n-decanoic acid, undecanoic acid, dodecanoic acid (lauric acid), etc. The C4-C12 thiol ligands include one or more of butyl mercaptan, hexyl mercaptan, 1-heptyl mercaptan, n-octyl mercaptan, isooctyl mercaptan, 1-decyl mercaptan, 1-undecyl mercaptan, 1-dodecanethiol, 1-pentyl mercaptan, etc. The C4-C12 amine ligands include one or more of n-butylamine, pentylamine, hexylamine, heptylamine, n-octylamine, decylamine, 1-aminoundecane, dodecylamine, etc. The C4-C12 phosphate ligands include one or more of n-hexyl phosphate, 1-octyl phosphate, 1-decyl phosphate, n-dodecyl phosphoric acid, etc.
[0046] Specifically, among the ligands connected to the zinc oxide or doped zinc oxide, the molar ratio of the long carbon chain ligand to all ligands on the surface of zinc oxide is greater than or equal to 20%. Specifically, it can be 20% to 50%, 20% to 30%, 30% to 40%, 40% to 50%, 20% to 70%, 20% to 80%, 20% to 90%, etc. It can be understood that the ligands connected to the surface of the zinc oxide or doped zinc oxide can be introduced through a reaction precursor, or can be introduced through an additional ligand reagent or ligand solvent, such as acetate ligands, hydroxyl ligands, etc. The molar ratio of the long chain ligand to all ligands is greater than or equal to 20%, that is, the number of the long chain ligands accounts for a percentage of the total number of ligands greater than or equal to 20%, which can prevent the surface contact between zinc oxide and the material of the light-emitting layer 30 through a steric hindrance effect.
[0047] In one embodiment, the thickness of the first electron transport layer 41 is 5-40 nm, specifically 5-35 nm, 10-35 nm, 10-30 nm, 15-30 nm, 15-25 nm, 20-25 nm, etc.
[0048] In one embodiment, the thickness of the second electron transport layer 42 is 5-40 nm, specifically 5-35 nm, 10-35 nm, 10-30 nm, 15-30 nm, 15-25 nm, 20-25 nm, etc.
[0049] In one embodiment, the first electron transport layer 41 may be composed of gallium-lithium co-doped zinc oxide. In other embodiments, the first electron transport layer 41 may also include other materials, such as conductive materials.
[0050] In one embodiment, the second electron transport layer 42 may be composed of the zinc oxide or doped zinc oxide. In other embodiments, the second electron transport layer 42 may also include other materials, such as conductive materials.
[0051] In one embodiment, the electronic functional layer further includes an electron injection layer 43, and the electron injection layer 43 is disposed close to the cathode 20, that is, the electron injection layer 43 is disposed between the cathode 20 and the first electrical transport layer 41. The material of the electron injection layer 43 includes one or more of LiF, LiF / Yb, MgP, MgF2, Al2O3, Ga2O3, ZnO, Cs2CO3, Rb2CO3, RbBr
[0052] In one embodiment, the material of the light-emitting layer 30 is selected from one or more of organic light-emitting materials and quantum dot materials.
[0053] The organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light.
[0054] The quantum dot material can be selected from at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, Cd At least one of ZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnP bTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, At least one of GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS;
[0055] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - When n=2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.
[0056] In a specific embodiment, the material of the light-emitting layer 30 is selected from the quantum dot material.
[0057] The thickness of the light emitting layer 30 may be 15 to 40 nm, specifically 15 to 35 nm, 25 to 35 nm, 25 to 30 nm, etc.
[0058] In one embodiment, the light emitting device 100 may further include a hole functional layer 50, and the hole functional layer 50 is disposed between the anode 10 and the light emitting layer 30. The hole functional layer 50 may include a hole injection layer 51 and / or a hole transport layer 52. When the hole functional layer 50 includes two layers, the hole injection layer 51 and the hole transport layer 52, the hole injection layer 51 is disposed close to the anode 10, and the hole transport layer 52 is disposed close to the light emitting layer 30.
[0059] In one embodiment, the thickness of the hole injection layer 51 may be 20-200 nm, specifically 20-150 nm, 80-150 nm, 80-120 nm, etc. The thickness of the hole transport layer 52 may be 30-180 nm, specifically 30-150 nm, 50-150 nm, 50-120 nm, 80-120 nm, 80-100 nm, etc.
[0060] The material of the hole transport layer 52 is selected from arylamine, polyaniline, polypyrrole, poly(p-)phenylene vinylene and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe3 , CuS, CuSCN; wherein the aromatic amine is selected from 4,4'-bis(9-carbazole)biphenyl (CBP), poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine) (TFB), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4 ,4',4"-tri(carbazol-9-yl)triphenylamine (TCATA), 4,4',4"-tri(N-carbazol-9-yl)triphenylamine (TCTA), 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl- One or more of 4,4'-diamine (NPB), Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), and spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV) and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV).
[0061] The material of the hole injection layer 51 is a material having hole injection capability, selected from poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN), copper phthalocyanine (CuPc ), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine (m-MTDATA), 4,4',4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with F4-TCNQ, p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, CuO; the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, CuS.
[0062] In one embodiment, the anode 10 and the cathode 20 are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, ITZ O, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS and ZnS / Al / ZnS. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three stacked layers consisting of an AZO layer, an Ag layer and an AZO layer.
[0063] In one embodiment, the anode 10 is composed of a conductive material with a relatively high work function, and may be composed of a doped or undoped metal oxide, such as ITO, IZO, ITZO, ICO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, Ga:SnO2 or AZO, etc.; or in addition to the above-mentioned metal oxides, it may be composed of a metal material including nickel (Ni), platinum (Pt), gold (Au), silver (Ag), iridium (Ir) or CNT.
[0064] In one embodiment, the cathode 20 is composed of a conductive material with a relatively low work function, which may be one or more of Ca, Ba, Ca / Al, LiF / Ca, LiF / Al, BaF2 / Al, CsF / Al, CaCO3 / Al, BaF2 / Ca / Al, Al, Mg, Au:Mg or Ag:Mg.
[0065] It is understandable that, in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices to help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer.
[0066] It can be understood that the material and thickness of each layer of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100 .
[0067] The light emitting device 100 further includes a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.
[0068] It can be understood that when the anode 10 or the cathode 20 is connected to the substrate, it can be called a bottom electrode, and the one away from the substrate is a top electrode, wherein the thickness of the bottom electrode can be 20 to 200 nm, and the thickness of the top electrode can be 40 to 190 nm.
[0069] It can be understood that the light emitting device 100 can be a normal light emitting device or an inverted light emitting device. When the light emitting device 100 is a normal light emitting device, the substrate is combined with the side of the anode 10 away from the light emitting layer 30. When the light emitting device 100 is an inverted light emitting device, the substrate is combined with the side of the cathode 20 away from the light emitting layer 30.
[0070] It is understandable that, in addition to the above-mentioned functional layers, the light-emitting device 100 may also be provided with some functional layers conventionally used in light-emitting devices to help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer.
[0071] It can be understood that the material and thickness of each layer of the light-emitting device 100 can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device 100 .
[0072] In the light-emitting device provided in the present application, the preparation methods of the anode 10, cathode 20, light-emitting layer 30, hole functional layer 50, electronic functional layer 40 and other film layers can be realized by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anodic oxidation method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, blade coating method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.
[0073] The present application also provides a method for preparing a light emitting device, see Figure 2 , Figure 2 The present invention provides a flow chart of a method for preparing a light-emitting device according to an embodiment of the present invention, which specifically includes the following steps:
[0074] Step S21: providing a preset device, wherein the preset device includes a cathode;
[0075] Step S22: forming an electronic functional layer on the preset device;
[0076] Step S23: forming a stacked light-emitting layer and an anode on the electronic functional layer.
[0077] The light-emitting device prepared in this embodiment is an inverted device.
[0078] See also Figure 3 , Figure 3 A schematic flow chart of another embodiment of a method for preparing a light-emitting device provided in the present application specifically includes the following steps:
[0079] Step S31: providing a preset device, wherein the preset device includes a stacked anode and a light-emitting layer;
[0080] Step S32: forming an electronic functional layer on the preset device;
[0081] Step S33: forming a cathode on the electronic functional layer.
[0082] The light-emitting device prepared in this embodiment is an upright device.
[0083] In the above two embodiments, the electronic functional layer includes a first electron transport layer and a second electron transport layer, the second electron transport layer is arranged close to the light-emitting layer, and the first electron transport layer is arranged away from the light-emitting layer;
[0084] The material of the first electron transport layer includes a first doped zinc oxide, and the material of the second electron transport layer includes zinc oxide or a second doped zinc oxide, and a long carbon chain ligand having 4 to 12 carbon atoms is connected to the zinc oxide or the second doped zinc oxide.
[0085] In the above two embodiments, an electronic functional layer including a first electron transport layer and a second electron transport layer is provided between the light-emitting layer and the cathode, wherein the zinc oxide in the second electron transport layer provided close to the light-emitting layer or the second doped zinc oxide is connected to a long carbon chain ligand with a carbon chain length of 4 to 12 carbon atoms, which can prevent the surface contact between zinc oxide and the material of the light-emitting layer through the steric hindrance effect, thereby inhibiting the dissociation of excitons at the interface between the light-emitting layer and the electronic functional layer, thereby improving the recombination efficiency and luminous efficiency of the light-emitting device, and also improving the life of the light-emitting device. The material in the first electron transport layer provided close to the cathode includes the first doped zinc oxide, which can improve the conductivity and reduce the work function, thereby increasing the electron mobility.
[0086] Specifically, the first doped zinc oxide, zinc oxide or the second doped zinc oxide, the long carbon chain ligand, etc. can refer to the relevant description of the light emitting device 100 mentioned above, and will not be repeated here.
[0087] In step S22:
[0088] In one embodiment, forming an electronic functional layer on the preset device specifically includes:
[0089] Step S221: providing a first solution, wherein the first solution includes a first metal source, an organic amine and a first solvent, and performing a reflux reaction on the first solution under an inert gas atmosphere to obtain a first sol; wherein the first metal source includes a first zinc source, a first doping metal source and a second doping metal source;
[0090] Step S222: placing the first sol on the preset device and performing annealing to obtain the first electron transport layer;
[0091] Step S223: providing a second solution, wherein the second solution includes zinc oxide nanomaterials and a second solvent, and disposing the second solution on the first electron transport layer to obtain the second electron transport layer;
[0092] Wherein, the zinc oxide nanomaterial is selected from zinc oxide or a second doped zinc oxide.
[0093] In step S32:
[0094] In one embodiment, forming an electronic functional layer on the preset device specifically includes:
[0095] Step S321: providing a second solution, wherein the second solution includes a zinc oxide nanomaterial and a second solvent, and placing the second solution on the preset device to obtain the second electron transport layer;
[0096] Step S322: providing a first solution, wherein the first solution includes a first metal source, an organic amine and a first solvent, and performing a reflux reaction on the first solution under an inert gas atmosphere to obtain a first sol; wherein the first metal source includes a first zinc source, a first doping metal source and a second doping metal source;
[0097] Step S323: placing the first sol on the second electron transport layer, and performing annealing treatment to obtain the first electron transport layer.
[0098] In the electronic functional layer prepared in the above two embodiments, the first electron transport layer is arranged close to the cathode, and the second electron transport layer is arranged close to one side of the light-emitting layer. The first electron transport layer is prepared by the sol-gel method, which can improve the effective incorporation of the first doped metal and the second doped metal, and the sol-gel method can significantly improve the crystallinity of the film layer after high-temperature annealing process, thereby improving the electron mobility of the first electron transport layer. The second electron transport layer is prepared by the solution method to improve the flatness of the entire electronic functional layer.
[0099] In the step S221 and step S322:
[0100] The first zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, zinc laurate and zinc oxide.
[0101] In one embodiment, the first doping metal source includes one or more of a Li source, a Be source, a Mg source, an Al source, a K source, and a Ca source.
[0102] The Li (lithium) source includes one or more of lithium acetate and its hydrate, lithium nitrate and its hydrate, lithium sulfate and its hydrate, lithium chloride and its hydrate, and the like.
[0103] The Be (beryllium) source includes one or more of beryllium acetate and its hydrate, beryllium nitrate and its hydrate, beryllium sulfate and its hydrate, beryllium chloride and its hydrate, and the like.
[0104] The Mg source includes one or more of magnesium acetate and its hydrate, magnesium nitrate and its hydrate, magnesium sulfate and its hydrate, magnesium chloride and its hydrate, and the like.
[0105] The Al source includes one or more of aluminum acetate and its hydrate, aluminum nitrate and its hydrate, aluminum sulfate and its hydrate, aluminum chloride and its hydrate, and the like.
[0106] The K source includes one or more of potassium acetate and its hydrate, potassium nitrate and its hydrate, potassium sulfate and its hydrate, potassium chloride and its hydrate, and the like.
[0107] The Ca source includes one or more of calcium acetate and its hydrate, calcium nitrate and its hydrate, calcium sulfate and its hydrate, calcium chloride and its hydrate, and the like.
[0108] Further, the molar ratio of the first doping metal element in the first doping metal source to the metal element in the first metal source is (1-20):100, specifically (1-15):100, (5-15):100, (5-13):100, (8-13):100, (8-10):100, etc. The metal element in the first metal source is the sum of zinc, the first doping metal and the second doping metal.
[0109] In one embodiment, the second doping metal source includes one or more of a Ga source, a Cd source, an In source, and a Sn source.
[0110] The Ga (gallium) source includes one or more of gallium nitrate and its hydrate, gallium sulfate and its hydrate, and gallium chloride and its hydrate.
[0111] The Cd (cadmium) source includes one or more of cadmium nitrate and its hydrate, cadmium sulfate and its hydrate, cadmium chloride and its hydrate.
[0112] The In (indium) source includes one or more of indium nitrate and its hydrate, indium sulfate and its hydrate, indium chloride and its hydrate.
[0113] The Sn source includes one or more of indium nitrate and its hydrate, indium sulfate and its hydrate, indium chloride and its hydrate.
[0114] The molar ratio of the gallium element in the gallium source to the metal element in the first metal source is (1-20):100, specifically (1-15):100, (5-15):100, (5-13):100, (8-13):100, (8-10):100, etc. The metal element in the first metal source is the sum of zinc, gallium and lithium.
[0115] In one embodiment, in the first solution, the molar concentration of the total metal elements is 0.1-1 mmol / mL, that is, the molar concentration of the metal elements in the first metal source is 0.1-1 mmol / mL, specifically 0.1-0.85 mmol / mL, 0.25-0.85 mmol / mL, 0.25-0.5 mmol / mL, etc. The concentration is conducive to the formation of a sol, has good dispersibility in the process of forming the first electron transport layer, and improves the film-forming property of the first electron transport layer. It can be understood that the total metal elements include all metal elements of the first solution, including the sum of zinc, gallium and lithium.
[0116] The organic amine may include one or more of ethanolamine, diethanolamine, 3-aminopropanol, etc. The organic amine may be used as a stabilizer when the first solution is subjected to a reflux reaction, and the stabilizer may complex with the precursor to improve the dispersion and stability of the precursor and prevent agglomeration during the system reflux.
[0117] In one embodiment, the molar ratio of the organic amine to the first metal source is 1:1.3 to 1.3:1, specifically 1:1.3 to 1.2:1, 1:1.2 to 1.2:1, 1:1.2 to 1.1:1, 1:1.1 to 1.1:1, 1:1.1 to 1.1, etc.
[0118] The first solvent is selected from alcohol solvents, and specifically may include one or more of ethanol, isopropanol, n-butanol, 2-methoxyethanol, and the like.
[0119] In one embodiment, the reflux reaction temperature is 50-80° C., specifically 50-75° C., 55-75° C., 55-70° C., 60-70° C., 60-65° C., etc. The first solution undergoes a reflux reaction within the above temperature range to gradually form a clear first sol.
[0120] In one embodiment, the reflux reaction time may be 3 to 12 hours, specifically 3 to 10 hours, 5 to 10 hours, 5 to 8 hours, etc.
[0121] In the step S222 and step S323:
[0122] After the first sol is formed into a wet film, the first electron transport layer is obtained by annealing, wherein the temperature of the annealing is 150-500°C, specifically 150-200°C, 200-300°C, 300-400°C, 400-500°C, etc. The annealing at the high temperature above can significantly improve the crystallinity of the first electron transport layer, thereby improving the electron mobility of the first electron transport layer.
[0123] Furthermore, the annealing treatment time may be 5 to 120 minutes, specifically 5 to 30 minutes, 30 to 60 minutes, 60 to 90 minutes, 90 to 120 minutes, etc.
[0124] In one embodiment, the annealing process may be performed in a dry atmosphere, wherein the dry atmosphere contains oxygen, so as to form gallium-lithium co-doped zinc oxide. Specifically, the dry atmosphere may be a dry air atmosphere.
[0125] In the step S223 and step S321:
[0126] After the second solution is set, drying is also included to obtain the second electron transport layer. The drying can be heating drying, the heating drying temperature is 60 to 150° C., and the time is 1 min to 30 min. The drying can be vacuum drying, and the vacuum drying pressure is 10 -1 ~10 -2 Pa, the temperature is 0-30°C, for example, it can be at room temperature about 25°C.
[0127] The zinc oxide nanomaterial is selected from zinc oxide or doped zinc oxide. Specifically, a long carbon chain ligand with a carbon chain length of 4 to 12 carbon atoms is connected to the zinc oxide or doped zinc oxide. Further, among the ligands connected to the zinc oxide or doped zinc oxide, the molar ratio of the long carbon chain ligand to all ligands on the surface of zinc oxide is greater than or equal to 20%. For details, please refer to the relevant description in the light-emitting device 100, which will not be repeated here.
[0128] The second solvent is selected from alcohol solvents, and specifically may include one or more of ethanol, isopropanol, n-butanol, 2-methoxyethanol, and the like.
[0129] In the second solution, the concentration of the zinc oxide nanomaterial is 10-50 mg / mL, specifically 10-45 mg / mL, 15-45 mg / mL, 15-40 mg / mL, 20-40 mg / mL, 20-35 mg / mL, 25-35 mg / mL, etc.
[0130] In one embodiment, the zinc oxide or doped zinc oxide is prepared by a low temperature alcohol phase method. Specifically, the preparation of zinc oxide or doped zinc oxide specifically includes the following steps:
[0131] Providing a third solution, the third solution comprising a second metal source, a ligand solvent and a third solvent, wherein the second metal source comprises a second zinc source or the second metal source comprises a second zinc source and a doping metal source, and the carbon chain length of the ligand solvent is 4 to 12 carbon atoms;
[0132] Adding alkali to the third solution, mixing and reacting at room temperature to obtain zinc oxide or doped zinc oxide.
[0133] The second zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, zinc laurate, etc. The doping metal source is selected from corresponding metal salts according to the type of doping metal, which is not limited here.
[0134] The third solvent includes one or more of dimethyl sulfoxide, NN-dimethylformamide, tetrahydrofuran, and alcohol solvents, wherein the alcohol solvent includes one or more of methanol, ethanol, isopropanol, and the like.
[0135] In one embodiment, the ligand solvent includes one or more of a C4-C12 carboxylic acid solvent, a C4-C12 thiol solvent, a C4-C12 amine solvent, and a C4-C12 phosphoric acid solvent.
[0136] Specifically, the C4-C12 carboxylic acid solvent includes one or more of butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, n-octanoic acid, n-decanoic acid, undecanoic acid, dodecanoic acid (lauric acid), etc. The C4-C12 mercaptan solvent includes one or more of butyl mercaptan, hexyl mercaptan, 1-heptyl mercaptan, n-octyl mercaptan, isooctyl mercaptan, 1-decyl mercaptan, 1-undecyl mercaptan, 1-dodecanethiol, 1-pentyl mercaptan, etc. The C4-C12 amine solvent includes one or more of n-butylamine, pentylamine, hexylamine, heptylamine, n-octylamine, decylamine, 1-aminoundecane, dodecylamine, etc. The C4-C12 phosphoric acid solvent includes one or more of n-hexyl phosphoric acid, 1-octyl phosphoric acid, 1-decyl phosphoric acid, n-dodecyl phosphoric acid, etc.
[0137] It can be understood that the second metal source includes a second metal cation and a second anion, wherein the second metal cation includes a zinc ion and a doped metal ion.
[0138] In one embodiment, the molar ratio of the ligand solvent to the second anion is greater than or equal to 40%, specifically 40% to 60%, 60% to 70%, 70% to 80%, etc. The molar ratio of the ligand solvent to the second anion can make the molar ratio of the long-chain ligand connected to the surface of the finally formed zinc oxide or doped zinc oxide to all ligands greater than or equal to 20%, wherein the long-chain ligand is a ligand with a carbon chain length of 4 to 12 carbon atoms.
[0139] The base may include one or more of lithium hydroxide, sodium hydroxide, triethylamine, etc. It is understood that the base may be added in the form of a base solution.
[0140] The mixing reaction time may be 5 to 15 hours, specifically 5 to 12 hours, 8 to 12 hours, 8 to 10 hours, etc.
[0141] In one embodiment, the method for preparing the light-emitting device further includes: forming a hole functional layer between the light-emitting layer and the anode.
[0142] In each embodiment of the above preparation method, the first electron transport layer, the second electron transport layer, the light-emitting layer, the hole functional layer, the cathode, the anode, etc. can all refer to the corresponding description in the light-emitting device 100 in the previous text, and will not be repeated here.
[0143] In the light-emitting device provided in the present application, the preparation method of the anode, cathode, light-emitting layer, hole functional layer and other film layers can be realized by conventional techniques in the art, such as chemical method or physical method. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, anodic oxidation method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, blade coating method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.
[0144] It is understood that the method for preparing the light-emitting device may further include a packaging step, and the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with ultraviolet curing glue. The concentration of oxygen and water in the environment of the packaging step is less than 0.1ppm to ensure the stability of the light-emitting device.
[0145] The present application also relates to a display device, which includes the light-emitting device provided in the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.
[0146] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0147] Device Example 1
[0148] The device embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.
[0149] Step 1: Add 0.4mmol zinc acetate dihydrate, 0.05mmol lithium acetate and 0.05mmol hydrated gallium nitrate to 30mL 2-methoxyethanol, then add 0.5mmol ethanolamine as a stabilizer, reflux at 50°C for 8 hours under an inert gas atmosphere, cool the solution after clarification to obtain a sol. Provide a substrate with a bottom electrode (cathode), deposit the above sol on the bottom electrode to form a film, and heat it at 300°C in dry air for 10mins and then anneal it to obtain a first electron transport layer with a thickness of 15nm.
[0150] Step 2: Add 10mmol zinc acetate dihydrate, 1mmol magnesium acetate tetrahydrate and 2mmol n-octylamine (ligand solvent) to 30ml dimethyl sulfoxide, stir at 60°C for 2 hours to obtain a zinc-magnesium precursor; add 15mmol lithium hydroxide to 30ml ethanol, stir at room temperature for 2 hours and ultrasonicate for 10 minutes to obtain an oxygen precursor; mix the zinc and magnesium precursors with the oxygen precursor at room temperature and stir for 10 hours, repeatedly centrifuge and disperse with ethanol and butanol to obtain a purified magnesium-doped zinc oxide solution containing long-chain ligands. The above magnesium-doped zinc oxide solution is deposited on the first electron transport layer, and a second electron transport layer with a thickness of 15nm is formed after removing the solvent.
[0151] Step 3: Dispose green quantum dots on the second electron transport layer to obtain a light-emitting layer with a thickness of 15 nm.
[0152] Step 4: In an inert atmosphere, spin-coat TFB (concentration of 8 mg / mL) on the light-emitting layer at a rotation speed of 3000 rpm for 30 s, and dry to remove the solvent to obtain a hole transport layer with a thickness of 80 nm.
[0153] Step 5: Spin-coat PEDOT:PSS on the hole transport layer at a rotation speed of 4000 rpm for 30 seconds, and dry to remove the solvent to obtain a hole injection layer with a thickness of 90 nm.
[0154] Step 6: By thermal evaporation, the vacuum degree is not higher than 3×10 -4 Pa, Ag was evaporated on the electron transport layer to obtain an anode with a thickness of 60 nm, and then encapsulated.
[0155] Device Example 2
[0156] This device embodiment is basically the same as device embodiment 1, with the only difference being that the thickness of the first electron transport layer is 20 nm, the thickness of the second electron transport layer is 10 nm, and the light-emitting layer is blue quantum dots instead of green quantum dots.
[0157] Device Example 3
[0158] This device example is substantially the same as device example 1, except that the ligand solvent in step 2 is dodecanoic acid instead of n-octylamine.
[0159] Device Example 4
[0160] This device example is substantially the same as device example 1, except that the ligand solvent in step 2 is butanethiol instead of n-octylamine.
[0161] Device Example 5
[0162] This device example is substantially the same as device example 1, except that the ligand solvent in step 2 is 1-decylphosphoric acid instead of n-octylamine.
[0163] Device Example 6
[0164] This device embodiment is basically the same as device embodiment 1, with the only difference being that in step 1, gallium-lithium co-doped zinc oxide nanomaterial is prepared by the method in step 2, and is disposed on the bottom electrode, and the solvent is removed to form a first electron transport layer with a thickness of 15 nm.
[0165] Device Comparative Example 1
[0166] The device comparison example is basically the same as device embodiment 1, with the only difference being that in step 1, the thickness of the first electron transport layer is 30 nm, the preparation of the second electron transport layer in step 2 is not performed, and the light-emitting device finally formed includes only the first electron transport layer, and does not include the second electron transport layer.
[0167] Device Comparison Example 2
[0168] This device embodiment is basically the same as device embodiment 1, with the only difference being that: step 1 is not performed, and the preparation of the second electron transport layer in step 3 is performed directly on the cathode, and a second electron transport layer with a thickness of 30 nm is formed, and the light-emitting device finally formed only includes the second electron transport layer, and does not include the first electron transport layer.
[0169] Device Comparison Example 3
[0170] This device embodiment is basically the same as device embodiment 2, with the only difference being that step 1 is not performed, and the preparation of the second electron transport layer in step 3 is performed directly on the cathode, and a second electron transport layer with a thickness of 30 nm is formed, and the light-emitting device finally formed only includes the second electron transport layer, and does not include the first electron transport layer.
[0171] Experimental example
[0172] The quantum dot light-emitting diodes of device embodiments 1-6 and device comparison examples 1-2 were tested, specifically including the turn-on voltage V@1nit, the maximum device efficiency CE@max at a current of 2mA, and the device life T95-1000 nit. The test data are shown in Table 1.
[0173] The device life refers to the time required for the brightness of the device to decrease to a certain proportion of the maximum brightness when the device is driven by a constant current or voltage. The time when the brightness drops to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually carried out by accelerating device aging at high brightness with reference to the OLED device test, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula, for example: the life under 1000nit is calculated as T95-1000 nit. The specific calculation formula is as follows:
[0174]
[0175] Where T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, for OLED, the value is usually 1.6~2. In this experiment, the lifespan of several groups of QLED devices at rated brightness was measured and the A value was 1.7.
[0176] The life test system is used to carry out life test on the corresponding devices. The test conditions are: at room temperature and the air humidity is 30-60%.
[0177] Table 1
[0178] V@1nit(V) CE@max(cd / A) T95-1000 nit(h) Device Example 1 3.7 125 4.5k Device Example 2 4.2 10 50 Device Example 3 4.5 132 2.8k Device Example 4 3.2 117 4.2k Device Example 5 5.5 135 3.1k Device Example 6 3.9 108 2.2k Device Comparison Example 1 2.5 70 2.0k Device Comparison Example 2 7.1 120 1.7k Device Comparison Example 3 8.0 7.6 12
[0179] Here, k represents thousand, for example, 4.5k=4500.
[0180] It can be seen from Table 1 that compared with device comparison examples 1 and 2, the quantum dot light-emitting diodes of device embodiments 1, 3-6 have relatively low turn-on voltages, as well as good luminous efficiency and lifespan. Compared with device comparison example 3, the quantum dot light-emitting diodes of device embodiment 2 have relatively low turn-on voltages, as well as good luminous efficiency and lifespan, indicating the setting of the two-layer electron transport layer in the present application. The first electron transport layer material close to the cathode includes zinc oxide or doped zinc oxide, and the zinc oxide or doped zinc oxide is connected to a long carbon chain ligand with a carbon chain length of 4 to 12 carbon atoms. The second electron transport layer material close to the light-emitting layer includes gallium-lithium co-doped zinc oxide, which can improve the recombination efficiency and luminous efficiency of the light-emitting device, reduce the turn-on voltage of the device, and improve the device efficiency and device life while ensuring that the device operating voltage does not increase significantly.
[0181] The light-emitting device and its preparation method, and the display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A light emitting device, characterized in that: include: An anode and a cathode arranged opposite to each other; A light-emitting layer is disposed between the anode and the cathode; An electronic functional layer, disposed between the cathode and the light-emitting layer; Among them, the electronic functional layer includes a first electron transport layer and a second electron transport layer, the first electron transport layer is arranged close to the cathode, and the second electron transport layer is arranged close to the light-emitting layer. The material of the first electron transport layer includes a first doped zinc oxide, and the material of the second electron transport layer includes zinc oxide or a second doped zinc oxide. The zinc oxide or the second doped zinc oxide is connected to a long carbon chain ligand with 4 to 12 carbon atoms.
2. The light emitting device according to claim 1, characterized in that: The first doped zinc oxide comprises zinc oxide, a first doping metal and a second doping metal, wherein the first doping metal comprises one or more of Li, Be, Mg, Al, K, and Ca, and the second doping metal comprises one or more of Ga, Cd, In, and Sn; and / or The second doped zinc oxide includes zinc oxide and a third doping element, and the third doping element includes one or more of Mg, Al, Ga, Li, K, Cd, In, and Sn.
3. The light emitting device according to claim 2, characterized in that: In the first electron transport layer, the molar ratio of the first doping metal to the total metal elements is (1-20):100; and / or In the first electron transport layer, the molar ratio of the second doping metal to the total metal elements is (1-20):
100.
4. The light emitting device according to claim 2, characterized in that: The long carbon chain ligand includes one or more of C4-C12 carboxylic acid ligands, C4-C12 sulfhydryl ligands, C4-C12 amine ligands, and C4-C12 phosphate ligands; and / or Among the ligands connected to the zinc oxide or doped zinc oxide, the molar ratio of the long carbon chain ligand to all the ligands on the surface of the zinc oxide is greater than or equal to 20%.
5. The light emitting device according to claim 4, characterized in that: The C4-C12 carboxylic acid ligands include one or more of butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, n-octanoic acid, n-decanoic acid, undecanoic acid, and dodecanoic acid; and / or The C4-C12 thiol ligands include one or more of butyl mercaptan, hexyl mercaptan, 1-heptyl mercaptan, n-octyl mercaptan, isooctyl mercaptan, 1-decyl mercaptan, 1-undecanethiol, 1-dodecanethiol, and 1-pentyl mercaptan; and / or The C4-C12 amine ligands include one or more of n-butylamine, pentylamine, hexylamine, heptylamine, n-octylamine, decylamine, 1-aminoundecane, and dodecylamine; and / or The C4-C12 phosphate ligand includes one or more of n-hexyl phosphate, 1-octyl phosphate, 1-decyl phosphate, and n-dodecyl phosphate.
6. The light emitting device according to claim 1, characterized in that: The first doped zinc oxide is selected from gallium-lithium co-doped zinc oxide, and one or more of n-octylamine, dodecanoic acid, butanethiol, and 1-decyl phosphoric acid are connected to the zinc oxide or the second doped zinc oxide.
7. The light emitting device according to claim 1, characterized in that: The thickness of the first electron transport layer is 5 to 40 nm; and / or The thickness of the second electron transport layer is 5 to 40 nm; and / or The material of the light-emitting layer is selected from one or more of organic light-emitting materials or quantum dot materials; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the Group II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZ nS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, Hg At least one of ZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb , at least one of GaPAs, GaPSb, AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNPs, InNAs, InNSb, InPAs, InPSb, GaAlNPs, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNPs, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNPs, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2 + , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or The cathode and the anode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, ITZO, ICO, A At least one of MO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS; and / or The light emitting device further comprises a hole functional layer, wherein the hole functional layer is arranged between the anode and the light emitting layer, and the hole functional layer comprises at least one layer of a hole injection layer and a hole transport layer, and the material of the hole transport layer is selected from arylamine, polyaniline, polypyrrole, poly(p-)phenylene vinylene and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives Its derivatives, poly (spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN one or more; wherein the aromatic amine is selected from 4,4'-bis (9-carbazole) biphenyl, poly (9,9-dioctylfluorene-CO-N- (4-butylphenyl) diphenylamine), poly (N,N'-bis (4-butylphenyl) -N,N'-bis (phenyl) benzidine), N,N'-bis (4- (N,N'-diphenyl-amino) triphenylamine, 4,4',4"-tri(carbazol-9-yl)triphenylamine, 4,4',4"-tri(N-carbazolyl)triphenylamine, 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, -diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, Spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene];The material of the hole injection layer is selected from poly(ethylenedioxythiophene): polystyrene sulfonate, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexycyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetra(4 -methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, 4,4',4"-tri[phenyl(m-tolyl)amino]triphenylamine, 4,4',4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with F4-TCNQ, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenylamine; -N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, one or more of transition metal oxides and transition metal sulfide compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3 and CuO; the metal sulfide compounds include one or more of MoS2, MoSe2, WS3, WSe3 and CuS; and / or The electronic functional layer also includes an electron injection layer, which is arranged close to the cathode, wherein the material of the electron injection layer includes one or more of LiF, LiF / Yb, MgP, MgF2, Al2O3, Ga2O3, ZnO, Cs2CO3, Rb2CO3, and RbBr.
8. A method for preparing a light emitting device, characterized in that: include: providing a cathode; Disposing an electronic functional layer on the cathode; forming a light-emitting layer on the electronic functional layer; forming an anode on the light-emitting layer; or, The preparation method comprises: Providing a preset device, the preset device comprising a stacked anode and a light-emitting layer; forming an electronic functional layer on the preset device; forming a cathode on the electronic functional layer; Among them, the electronic functional layer includes a first electron transport layer and a second electron transport layer, the first electron transport layer is arranged close to the cathode, and the second electron transport layer is arranged close to the light-emitting layer. The material of the first electron transport layer includes a first doped zinc oxide, and the material of the second electron transport layer includes zinc oxide or a second doped zinc oxide. The zinc oxide or the second doped zinc oxide is connected to a long carbon chain ligand with 4 to 12 carbon atoms.
9. The preparation method according to claim 8, characterized in that: The electronic functional layer is provided on the cathode, comprising: Providing a first solution and a second solution, wherein the first solution comprises a first metal source, an organic amine and a first solvent, wherein the first metal source comprises a first zinc source, a first doped metal source and a second doped metal source, and the second solution comprises a zinc oxide nanomaterial and a second solvent, wherein the zinc oxide nanomaterial is selected from zinc oxide or a second doped zinc oxide; reflux the first solution to obtain a first sol; The first sol is disposed on the cathode, and annealed to obtain the first electron transport layer; The second solution is disposed on the first electron transport layer to obtain the second electron transport layer; or, The forming of an electronic functional layer on the preset device comprises: Providing a first solution and a second solution, wherein the first metal source includes a first zinc source, a first doped metal source and a second doped metal source, and the second solution includes a zinc oxide nanomaterial and a second solvent, wherein the zinc oxide nanomaterial is selected from zinc oxide or a second doped zinc oxide; reflux the first solution to obtain a first sol; placing the second solution on the preset device to obtain the second electron transport layer; The first sol is disposed on the second electron transport layer, and annealing is performed to obtain the first electron transport layer.
10. The preparation method according to claim 8, characterized in that: The annealing temperature is 150-500°C; and / or The annealing treatment time is 5 to 120 minutes; and / or The annealing process is performed in a dry air atmosphere.
11. The preparation method according to claim 8, characterized in that: The temperature of the reflux reaction is 50-80°C; and / or The reflux reaction time is 3 to 12 hours; and / or The first zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, zinc laurate and zinc oxide; and / or The first doping metal source includes one or more of a Li source, a Be source, a Mg source, an Al source, a K source, and a Ca source; and / or The second doping metal source includes one or more of a Ga source, a Cd source, an In source, and a Sn source; and / or The molar ratio of the first doping metal element in the first doping metal source to the metal element in the first metal source is (1-20):100; and / or The molar ratio of the second doping metal element in the second doping metal source to the metal element in the first metal source is (1-20):100; and / or In the first solution, the molar concentration of the metal element in the first metal source is 0.1 to 1 mmol / mL; and / or The organic amine includes one or more of ethanolamine, diethanolamine, and 3-aminopropanol; and / or The molar ratio of the organic amine to the first metal source is 1:1.3 to 1.3:1; and / or The first solvent is selected from alcohol solvents.
12. The preparation method according to claim 8, characterized in that: The preparation method further comprises preparing a zinc oxide nano material, and the preparation of the zinc oxide nano material comprises: Providing a third solution, the third solution comprising a second metal source, a ligand solvent and a third solvent, wherein the second metal source comprises a second zinc source or the second metal source comprises a second zinc source and a third doping metal source, and the carbon chain length of the ligand solvent is 4 to 12 carbon atoms; Adding alkali to the third solution, mixing and reacting at room temperature to obtain zinc oxide or doped zinc oxide.
13. The preparation method according to claim 12, characterized in that: The ligand solvent includes one or more of a C4-C12 carboxylic acid solvent, a C4-C12 mercaptan solvent, a C4-C12 amine solvent, and a C4-C12 phosphoric acid solvent; and / or The second metal source comprises a second metal cation and a second anion, wherein a molar ratio of the ligand solvent to the second anion is greater than or equal to 40%; and / or The second zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, and zinc laurate; and / or The third solvent includes one or more of dimethyl sulfoxide, NN-dimethylformamide, tetrahydrofuran, and alcohol solvents; and / or The third doping metal source includes one or more of a Mg source, an Al source, a Ga source, a Li source, a K source, a Cd source, an In source, and a Sn source; and / or The base comprises one or more of lithium hydroxide, sodium hydroxide and triethylamine; and / or The mixing reaction time is 5 to 15 hours.
14. The preparation method according to claim 8, characterized in that: After the second solution is provided, the method further includes drying, wherein the drying is heating drying or vacuum drying, wherein the heating drying temperature is 60 to 150° C., and the vacuum drying pressure is 10 -1 ~10 -2 Pa, the vacuum drying temperature is 0 to 30°C; and / or The second solvent is selected from alcohol solvents; and / or In the second solution, the concentration of the zinc oxide nanomaterial is 10-50 mg / mL.
15. A display device, characterized in that: The invention comprises a light-emitting device as claimed in any one of claims 1 to 7, or a light-emitting device prepared by the preparation method as claimed in any one of claims 8 to 14.